An Efficient Supply Chain Management Model: The Analysis of Domestic and International Practices - Dobrovolskaya, Oksana; Stovolos, Nadiya; Lipatov, Andrey; Borisova, Uliana; Volodin, Oleg (International Journal of Supply Chain Management, 2020)
Abstract— The study discusses the challenge of providing an effective supply chain management model that would meet modern requirements. The purpose of the study is to analyze the theoretical and practical aspects of developing business processes of supply chain management, as well as to substantiate an efficient business logistics management model. The survey revealed that supply chain management is carried out in a highly competitive environment while business owners are in very difficult conditions: on the one hand, customer requirements are being expanded and diversified, and on the other hand, global logistics market entry requires better service and price cuts. It has been concluded that it is feasible to outsource IT logistics processes due to the global tendency to complicate supply chain management, the introduction of information technologies, increasing customer requirements, and major business processes within the supply chain. This is reflected through an increase in investment / demand in the IT industry, an increase in the number of providers, an increase in equipment, a shortage of specialists, etc. The trend observed in our country is consistent with the ones of developed economies. An algorithm for the implementation of the supply chain formation mechanism has been developed.